KAJIAN PENGELOLAAN INFRASTRUKTUR RUSUNAWA - Yunara, Rita (Jurnal Teknik Sipil, 2018)
Rusunawa was constructed with the aim to improve the quality of the settlement environment through rejuvenation, restoration, and relocation. The provision of low-cost apartments was originally intended to overcome horizontal slums, but unwittingly it has changed the slums, not only horizontally but also vertically. Seeing the declining in the quality of the environment, a study on the construction planning of low-cost apartments is necessary. Infrastructure and facilities play a major role in the sustainability of rusunawa. The aims of this study are to examine the infrastructure and facilities and to determine the strategies to improve them according to the prevailing standards. Data on water needs of the low-cost apartment residents were used to figure out the needs for clean water and to identify the condition and the capacity of the existing water facility in rusunawa based on the regulation. Data of the existing condition of drainage and the information of inundation around the rusunawa in rainy season were used to identify the drainage facility based on the regulation. A sample of waste was also obtained to analyze the BOD5, COD, TSS, pH, oil and fat parameter and then it was compared with the prevailing quality standards. Subsequently, this study identified the condition and the capacity of water waste based on the regulation. Afterwards, this study logged the garbage volume from the residents for 8 days which aimed to find out the garbage volume an to identify the condition and the capacity of waste facility based on the regulation. Later on, this study logged green open space facility, building transportation, and road facility to identify the existing condition based on the regulation. This research was conducted using descriptive qualitative analysis method. The results show that the infrastructure and the facility of low-cost apartments on Jl. Kom Yos Sudarso Jeruju is not optimal. The water waste facility has not met the prevailing standard and regulation. The construction of garbage dump has not implemented the regulation on waste segregation. Finally, the road facility has not complied the requirements.  Keywords: identification, infrastructure, facility, low-cost apartment.